Recent advances in injectable hydrogels for osteoarthritis treatments - Chen, Jiayi; Deng, Mingcong; Wang, Jiangliang; Liu, Yuanwen; Hu, Ziran; Luan, Feifan; Zhu, Huifeng; Zheng, Chenxiao (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoarthritis (OA) is a degenerative joint disease characterized by cartilage degradation, synovial inflammation, and subchondral bone alterations, poses significant challenges due to its high prevalence and associated disability. Injectable hydrogels have emerged as promising candidates for OA treatment due to their ability to deliver bioactive molecules directly to the affected joint, enhancing local efficacy while minimizing systemic side effects. This review focuses on recent advances in injectable hydrogels for OA treatment, emphasizing their structural design, functional properties, and therapeutic applications. We further discuss the advantages and limitations of natural, synthetic, and composite hydrogels, as well as innovative cross-linking strategies and stimuli-responsive behaviors. Thermosensitive, pH-responsive, enzyme-responsive, and multi-responsive hydrogels are highlighted for their potential to achieve intelligent drug delivery, inhibit cartilage degradation, and reduce inflammation. Overall, injectable hydrogels hold great promise for OA treatment and become an effective therapeutic option with further research and innovation.